The Influence of Consumer Behavior and Marketing Mix Based on Digital Marketing on Purchasing Decisions (Case Study of Shabby Pink Store Consumers in Medan City) - Sarah Melinda Sihombing; Nur Aisyah (International Journal of Managemen Analytics (IJMA), 2023)
This study aims to determine "The Influence of Consumer Behavior and Digital Marketing on Purchasing Decisions (Case Study on Shabby Pink Store consumers in Medan City)". Consumer behavior is defined as the dynamics of interaction between influence and awareness of behavior and the environment where humans exchange aspects of life and purchase decisions are actions taken by consumers who want to choose to buy one or more alternative products. This research uses a type of associative quantitative research. The samples in this study are respondents who have purchased products at the Shabby Pink store with a total sample of 103 respondents using a non-prob sampling technique. Sampling ability with purposive sampling approach and consumer criteria must buy at least 2x at the shabby pink store. Data collection was carried out by distributing questionnaires via Google Forms. Based on the results of the T-test it was found that Tiktok Affiliate Marketing Promotion had a positive and significant effect on purchasing decisions. In the Coefficient of Determination Test (R2), it can be seen that the Adjusted R Square value obtained is 0.753 (75.3%). This shows that the independent variable has a high ability to explain variations in the dependent variable (Purchase Decision) in this study. The remaining 24.7% will be affected by other factors that cannot be explained in this study.